A Methodology for Teaching Ordinary Differential Equations Trough the LIE Group Theory in Engineering Courses (2019)
This article presents a methodology that allows the introduction of the LIE theory in relation to first order ordinary differential equations for undergraduate engineering courses. The theoretical background needed is identified. A methodology was determined and the results of its application in the regular course of ODE’s are presented. It was found that the proposed methodology is adequate. The students exposed to this methodology interiorized the related concepts and were able to solve linear and not linear first order ODE’s analytically